(f+g)(5)=33 is the answer
Answer:
y = -5x + 4
Step-by-step explanation:
slope = -5x
y-intercept = 4
y = mx + b --> slope intercept formula
y = -5x + 4 --> final solution
-9-(12-3x)=-9-1*(12)-1*(-3)=-9-12+3x=-21+3x=3(x-7)
Answer: y = -4x
Step-by-step explanation: You would use the formula y = mx + b to solve your problem. When you plug the numbers in, you get y = -4x. There would be no "+ b" because in this case, the y-intercept (b) is equal to zero. Therefore, you would not need to write "y = -4x + 0" because that would not be the equation in its simplest form.
As per the isosceles triangle theorem, if the two base angles are congruent then the legs are also congruent, so we must set the two legs equal to each other:
2z - 15 = 9
Add 15 to both sides:
15 - 15 = 0
15 + 9 = 24
Divide 2 from each side:
2z = 24
2z/2 = z
24/2 = 12
z = 12
Hence, the answer would be D: z = 12